2012
DOI: 10.1159/000342335
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lean and Fat Body Mass, Bone Biomarkers and Gonadal Steroids with Bone Mass during Pre- and Midpuberty

Abstract: Background/Aims: The association of bone mass with body composition, bone turnover markers and gonadal steroids was examined in Hungarian children during pre- and midpuberty. Methods: Two hundred and thirty-seven 7- to 16-year-old subjects (56% girls) were investigated. Bone mineral density (BMD), fat mass and total and appendicular lean mass were estimated with dual-energy X-ray absorptiometry (Lunar Prodigy). The fat mass index and appendicular lean mass index (LMI) were calculated. Serum bone markers, parat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…These findings are consistent with the premise that bone markers reflect instantaneous metabolic activity and do not directly translate physical dimensions that result from the cumulative process of bone gain throughout several years [6]. In prepubertal children, some previous studies have also found no relationship between tALP, OC or β-CTx and whole body (WB) and LS BMC or BMD [14, 15, 35]. Other studies disclosed, however, consistent positive relationships between tALP and OC and WB and LS BMC, in boys [16] and between OC and CTX and WB and LS BMC/BMD, in both sexes [15, 17].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These findings are consistent with the premise that bone markers reflect instantaneous metabolic activity and do not directly translate physical dimensions that result from the cumulative process of bone gain throughout several years [6]. In prepubertal children, some previous studies have also found no relationship between tALP, OC or β-CTx and whole body (WB) and LS BMC or BMD [14, 15, 35]. Other studies disclosed, however, consistent positive relationships between tALP and OC and WB and LS BMC, in boys [16] and between OC and CTX and WB and LS BMC/BMD, in both sexes [15, 17].…”
Section: Discussionsupporting
confidence: 85%
“…Other studies disclosed, however, consistent positive relationships between tALP and OC and WB and LS BMC, in boys [16] and between OC and CTX and WB and LS BMC/BMD, in both sexes [15, 17]. In older pubertal children, inverse correlations between serum OC or CTX and BMD were disclosed [9, 15], which is expected because, during puberty, bone turnover decreases with advancing sexual maturation while, at the same time, bone mass accrual continues up to peak bone mass [7]. Some authors have also described site-specific associations between bone metabolism markers and bone mass during puberty, disclosing stronger relationships in anatomical sites with more trabecular bone (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results confirmed data in the literature on this bone marker [24] obtained for Korean children, showing that the higher the excess weight, the lower the level of osteocalcin. The significant and negative correlations between FM and the three bone biomarkers found in the present study in girls may reflect the complex interaction between bone biomarkers, bone mass and gonadal steroids during puberty [25]. These authors observed differences in the association between bone mass and osteocalcin when the pre-and mid-pubertal periods were compared, with the observation of an inverse relationship only in mid-puberty.…”
Section: Discussionsupporting
confidence: 46%
“…These authors observed differences in the association between bone mass and osteocalcin when the pre-and mid-pubertal periods were compared, with the observation of an inverse relationship only in mid-puberty. Another interesting result was related to the strength of the correlation between osteocalcin and total body bone mass, with an r value of −0.60 in eutrophic girls, while eutrophic boys had a correlation of −0.07 [25]. These results indicate differences in the magnitude of the impact of bone mass between sexes.…”
Section: Discussionmentioning
confidence: 92%